Reviewing the functions of ethylene in growth and central metabolism in tomato - Nascimento, Vitor de Laia (2017)
It is responsible for regulating various aspects of the plant life cycle, including seed germination, root initiation, root development, floral development, sexual determination, fruit ripening, senescence and responses to biotic and abiotic stresses. The biosynthetic pathway and the series of reactions to formation of ethylene are already well established. In addition, the ethylene signaling process is also well characterized in that receptors on the membranes recognize this gas and a signaling cascade is activated to the nucleus where ethylene responsive genes are expressed. Much is known about how phytohormones in general influence plant development or how it relates to the signaling and transduction of information that help these organisms to adapt to the most diverse conditions. On the other hand, little is known about its direct relationship with carbon metabolism. The main goal of this work was to provide an enhanced comprehension coupled with a revalidation of the functional role of ethylene as a growth-related phytohormone. Remarkably, the results described within this thesis further demonstrate that ethylene, plant growth and carbon metabolism are strictly associated. Interestingly, ethylene seems to act directly on plant growth by inhibit or, in absence of your perception, allow the increased growth in tomato plants. Thus, it was demonstrated that an exogenous application of this hormone is able to reduce plant growth coupled with several morphological and metabolic adjustments. By contrast, in tomato Never ripe mutant plants, that are ethylene insensitive, growth is fairly induced coupled with significant changes in carbon assimilation characterized by increases in photosynthesis and an extensive metabolic reprogramming. Finally, after revisiting the possible functions of ethylene as a plant growth regulator, we can conclude that a biphasic effect of ethylene occurs in tomato once opposite effects are exhibited on plant growth. It is reasonable to suggest that metabolic and biochemical mechanisms that govern these two phenomena are not necessarily opposites.